2016
DOI: 10.1371/journal.pone.0150440
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Glutamine Concentrations in Liver Failure

Abstract: BackgroundHigher than normal plasma glutamine concentration at admission to an intensive care unit is associated with an unfavorable outcome. Very high plasma glutamine levels are sometimes seen in both acute and chronic liver failure. We aimed to systematically explore the relation between different types of liver failure and plasma glutamine concentrations.MethodsFour different groups of patients were studies; chronic liver failure (n = 40), acute on chronic liver failure (n = 20), acute fulminant liver fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 15 publications
3
29
0
Order By: Relevance
“…A SAPS II score higher than 32 revealed to be a predictive factor of severe hypoglutaminemia with high sensitivity and negative predictive values. Positive correlations between glutaminemia at admission and hepatic SOFA scores at admission and at the third and sixth days were in concordance with the association between liver dysfunction and high plasma glutamine concentrations described in the literature (31). The present findings did not corroborate the inverse correlation between admission glutaminemia and C-reactive protein levels observed by Nienaber A et al (32) in a mixed ICU patients cohort.…”
Section: Exogenous Glutamine Administration Is One Of the Most Controsupporting
confidence: 85%
See 2 more Smart Citations
“…A SAPS II score higher than 32 revealed to be a predictive factor of severe hypoglutaminemia with high sensitivity and negative predictive values. Positive correlations between glutaminemia at admission and hepatic SOFA scores at admission and at the third and sixth days were in concordance with the association between liver dysfunction and high plasma glutamine concentrations described in the literature (31). The present findings did not corroborate the inverse correlation between admission glutaminemia and C-reactive protein levels observed by Nienaber A et al (32) in a mixed ICU patients cohort.…”
Section: Exogenous Glutamine Administration Is One Of the Most Controsupporting
confidence: 85%
“…Severe glutamine depletion in critically ill patients, with plasma levels under 420 µmol/l, has been considered as a pejorative prognostic factor (2,3) and has demonstrated a variable prevalence, described between 25 and 67% (1,12,30,31). In addition, high baseline plasma concentrations of glutamine have been also associated with increased mortality rate.…”
Section: Exogenous Glutamine Administration Is One Of the Most Contromentioning
confidence: 99%
See 1 more Smart Citation
“…Oudemans-van Straaten et al [17] also reported low glutamine levels with a narrow range for the sepsis group, although the patients with sepsis in their study also had some outliers. Other groups have also reported on liver failure patients having elevated glutamine levels [16], with Helling et al [24] reporting a correlation between plasma glutamine levels and severity of liver disease. The former group proposed that liver glutamine uptake is reduced in cases of liver damage, resulting in raised plasma levels [16].…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, in a study of consecutive patients admitted to the ICU, an association between hyperglutaminemia at ICU admittance and an unfavorable outcome was seen [12]. On the contrary, no general connection between hyperglutaminemia at ICU admission and an unfavorable outcome could be demonstrated in a selected population of only patients with liver failure [28]. …”
Section: Plasma Glutamine As Proxymentioning
confidence: 99%